Acquired resistance of human T cells to sulfasalazine: stability of the resistant phenotype and sensitivity to non-related DMARDs. Issue 2 (13th January 2004) - van der Heijden, J; de Jong, M C; Dijkmans, B A C; Lems, W F; Oerlemans, R; Kathmann, I; Scheffer, G L; Scheper, R J; Assaraf, Y G; Jansen, G
Abstract : Background: A recent study from our laboratory showed that induction of the multidrug resistance related drug efflux pump ABCG2 contributed to acquired resistance of human T cells to the disease modifying antirheumatic drug (DMARD) sulfasalazine (SSZ). Objectives: To investigate the duration of SSZ resistance and ABCG2 expression after withdrawal of SSZ and rechallenging with SSZ, and to assess the impact of SSZ resistance on responsiveness to other DMARDs. Methods: Human CEM cells (T cell origin) with acquired resistance to SSZ (CEM/SSZ) were characterised for ( a ) SSZ sensitivity and ABCG2 expression during withdrawal and rechallenge of SSZ, and ( b ) antiproliferative efficacy of other DMARDs. Results: ABCG2 protein expression was stable for at least 4 weeks when CEM/SSZ cells were grown in the absence of SSZ, but gradually declined, along with SSZ resistance levels, to non-detectable levels after withdrawal of SSZ for 6 months. Rechallenging with SSZ led to a rapid (<2.5 weeks) resumption of SSZ resistance and ABCG2 expression as in the original CEM/SSZ cells. CEM/SSZ cells displayed diminished sensitivity to the DMARDs leflunomide (5.1-fold) and methotrexate (1.8-fold), were moderately more sensitive (1.6–2.0 fold) to cyclosporin A and chloroquine, and markedly more sensitive (13-fold) to the glucocorticoid dexamethasone as compared with parental CEM cells. Conclusion: The drug efflux pump ABCG2 has a major role in conferring resistance to SSZ. The collateral sensitivity of SSZ resistant cells for some other (non-related) DMARDs may provide a further rationale for sequential mono- or combination therapies with distinct DMARDs upon decreased efficacy of SSZ.